Online learning tool of basic alphabets with vocabulary for preschool students using tracing technique / Nurul Izzati Ab Satar - Ab Satar, Nurul Izzati (2017)
Preschool is the place where the children have their first experience in learning and playing with friends and teachers. Parents send their children who have no knowledge how to write and how to read to school. The children have problem to write the alphabet in correct technique. Even they can read the alphabet, the still have problem in writing. This learning tool is to help the preschool student to be able to write alphabets correctly using tracing technique where the students have to trace from point to point to form an alphabet. The learning tool had developed using Adobe Flash Professional CS5, Adobe Photoshop and Hypertext Markup Language (HTML). Adobe Flash is used for implement the tracing technique while Adobe Photoshop is used for image editing and HTML is used for web development. The evaluation method used was functionality of use and interactivity of learning. There are eight students from Pusat Perkembangan Kanak-Kanak Sri Ayu who are participating to test this learning tool. The result shows that most of respondents satisfied with the application.